Book review: Marquis R.J. & Koptur S. (eds) 2022: Caterpillars in the Middle. Tritrophic Interactions in a Changing World. - M. RINDOŠ (European Journal of Entomology)
Marquis R.J. & Koptur S. (eds) 2022: Caterpillars in the Middle. Tritrophic Interactions in a Changing World. Springer Nature Switzerland AG, xx + 642 pp. ISBN 978-3-030-86687-7. Hardcover. Price EUR 42.79.